2020
DOI: 10.1152/jn.00561.2019
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical balance and inhibition at the subacute stage after stroke

Abstract: Magnetic resonance spectroscopy indicated higher excitation-inhibition ratios within motor cortex during subacute recovery than age-similar healthy controls. Measures obtained from adaptive threshold hunting paired-pulse transcranial magnetic stimulation indicated greater tonic inhibition in patients compared with controls. Therapeutic approaches that aim to normalize motor cortex inhibition during the subacute stage of recovery should be explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 84 publications
0
15
1
Order By: Relevance
“…Interpretation of this result is not simple: the authors also reported higher GABA B activity (LICI) in both hemispheres compared with controls, in contradiction to previous studies 53 , 54 . Compared with controls, there was also an increase in 1 ms SICI, a putative measure of extra-synaptic activity, in the ipsilesional hemisphere at 6 weeks post-stroke, though this was not present at either 2 weeks or 12 weeks post-stroke 52 .…”
Section: Excitation–inhibition Balance In Stroke Pathophysiologymentioning
confidence: 70%
See 1 more Smart Citation
“…Interpretation of this result is not simple: the authors also reported higher GABA B activity (LICI) in both hemispheres compared with controls, in contradiction to previous studies 53 , 54 . Compared with controls, there was also an increase in 1 ms SICI, a putative measure of extra-synaptic activity, in the ipsilesional hemisphere at 6 weeks post-stroke, though this was not present at either 2 weeks or 12 weeks post-stroke 52 .…”
Section: Excitation–inhibition Balance In Stroke Pathophysiologymentioning
confidence: 70%
“…Furthermore, in a recent relatively small study, MRS-derived measurements of [GABA] in ipsilesional M1 were not significantly different from those in healthy age-matched controls, but [GABA] in the contralesional M1 was significantly lower, leading to an overall higher excitation–inhibition ratio 52 . Interpretation of this result is not simple: the authors also reported higher GABA B activity (LICI) in both hemispheres compared with controls, in contradiction to previous studies 53 , 54 .…”
Section: Excitation–inhibition Balance In Stroke Pathophysiologymentioning
confidence: 71%
“…The study data were drawn from a pool of patients admitted to our hospital between December 2009 and July 2019, who were enrolled in one of five different longitudinal studies ( Stinear et al, 2014 , Stinear et al, 2017a , Stinear et al, 2017b , Cirillo et al, 2020 , two unpublished). Exclusion criteria for all studies were age less than 18 years, bilateral or cerebellar stroke, and impaired cognition or communication precluding informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…Motor thresholds reflect the strength and size of the most excitable elements of the muscle representation in the primary motor area, which include the availability of excitatory neurotransmitters (e.g., glutamate) and their receptors and function of ion channels in cortical and spinal neuron populations [10]. Inability to obtain a MEP during TMS suggests poorer integrity of the corticospinal tract [12]. In this way, an increase in motor threshold (i.e., the primary motor area requires higher stimulation intensity to elicit a MEP) indicates decreased CSE.…”
Section: Motor Thresholdsmentioning
confidence: 99%